Chelation versus Non‐Chelation Control in the Stereoselective Alkenyl sp2 C−H Bond Functionalization Reaction. (30th March 2017) - Liang, Qiu‐Ju; Yang, Chao; Meng, Fei‐Fan; Jiang, Bing; Xu, Yun‐He; Loh, Teck‐Peng
Abstract: A hydroxy group chelation‐assisted stereospecific oxidative cross‐coupling reaction between alkenes was developed under mild reaction conditions. In the presence of palladium catalyst, the alkenes tethered with hydroxy functionality can couple efficiently with electron‐deficient alkenes to form the corresponding multi‐substituted olefin products. The hydroxy group on the substrate could play dual roles in reaction, acting as the directing group for alkenyl C−H bond activation and controlling the stereoselectivity of the products.